2021
DOI: 10.3390/cancers13081826
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA Early Kinetics Predict Response of Metastatic Melanoma to Anti-PD1 Immunotherapy: Validation Study

Abstract: The ability of early (first weeks of treatment) ctDNA kinetics to identify primary resistance to anti-PD1 immunotherapies was evaluated with a validation cohort of 49 patients treated with anti-PD1 for metastatic BRAF or NRAS-mutated melanoma, alone and pooled with the 53 patients from a previously described derivation cohort. BRAF or NRAS mutations were quantified on plasma DNA by digital PCR at baseline and after two or four weeks of treatment. ctDNA kinetics were interpreted according to pre-established bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…PET/CT imaging has shown tumor responses with 4–6 weeks of treatment with ICIs in melanoma patients ( 118 ). Sample collection at 2 weeks following treatment found changes in ctDNA that correlated with outcome in ICI therapy of melanoma patients, but earlier time points were not collected ( 75 ). It possible that changes in ctDNA in response to treatment existed sooner, again, earlier, high-frequency sampling is needed to test such hypotheses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PET/CT imaging has shown tumor responses with 4–6 weeks of treatment with ICIs in melanoma patients ( 118 ). Sample collection at 2 weeks following treatment found changes in ctDNA that correlated with outcome in ICI therapy of melanoma patients, but earlier time points were not collected ( 75 ). It possible that changes in ctDNA in response to treatment existed sooner, again, earlier, high-frequency sampling is needed to test such hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which ctDNA levels might be directly affected by tumor cell targeting and/or clearance by immune cells is still an open question. Evidence for this phenomenon however, might be found in studies where ctDNA levels spike within 2 weeks of immune-therapy initiation in metastatic melanoma patients, if and only if, the tumors were responsive ( 75 ).…”
Section: Biological Factors That Most Affect Circulating Tumor Dna Ab...mentioning
confidence: 99%
See 1 more Smart Citation
“…These found that a significant drop in ctDNA levels was associated with clinical response to immunotherapy and prolonged survival [72,73]. These findings have also been validated in metastatic melanoma by digital droplet PCR (ddPCR), where quantitative monitoring of ctDNA revealed that an increase in ctDNA levels by weeks 2 or 4 of treatment was associated with no clinical benefit and eventual disease progression, while no increase in ctDNA was associated with better OS, PFS, and durable clinical benefit [74][75][76]. In NSCLC patients that have undergone primary tumour resection, ctDNA quantification showed that higher plasma ctDNA levels were associated with a worse OS, and increased ctDNA levels could be observed shortly before a patient experienced a relapse [77].…”
Section: Ciculating Tumour Dnamentioning
confidence: 88%
“…An increasing number of studies are using ctDNA mutation analysis to select patients who will benefit from targeted therapy. For various cancer types, circulating tumor DNA profiling has been assessed for select cases who will benefit from therapy and to detect primary resistance to these therapies [36][37][38]. The cobas ® EGFR Mutation Test v2 was the first PCR-based assay approved by the U.S. Food and Drug Administration (FDA) using circulating cfDNA for the detection of mutations in the epidermal growth factor receptor (EGFR) gene to identify patients with metastatic NSCLC eligible for treatment with the TKI erlotinib [2,39].…”
Section: Monitoring and Treatment Selectionmentioning
confidence: 99%